Picosecond Laser Surface Texturing of a Stavax Steel Substrate for Wettability Control. (December 2018) - Wang, Xincai; Zheng, Hongyu; Wan, Yinchi; Feng, Wenhe; Lam, Yee Cheong
Abstract: In this investigation, a picosecond laser was employed to fabricate surface textures on a Stavax steel substrate, which is a key material for mold fabrication in the manufacturing of various polymer products. Three main types of surface textures were fabricated on a Stavax steel substrate: periodic ripples, a two-scale hierarchical two-dimensional array of micro-bumps, and a micro-pits array with nano-ripples. The wettability of the laser-textured Stavax steel surface was converted from its original hydrophilicity into hydrophobicity and even super-hydrophobicity after exposure to air. The results clearly show that this super-hydrophobicity is mainly due to the surface textures. The ultrafast laser-induced catalytic effect may play a secondary role in modifying the surface chemistry so as to lower the surface energy. The laser-induced surface textures on the metal mold substrates were then replicated onto polypropylene substrates via the polymer injection molding process. The surface wettability of the molded polypropylene was found to be changed from the original hydrophilicity to super-hydrophobicity. This developed process holds the potential to improve the performance of fabricated plastic products in terms of wettability control and easy cleaning.